Analysis of the Application of Character Education in Genetic Engineering Materials - Tomi Hidayat; Irwandi Irwandi; Nasral Nasral; Lely Yenita Asmara (Postgraduate, University of Mataram, 2022)
This study aims to analyze the application of character education in learning biology in Genetic Engineering material at State Senior High School 7 Bengkulu and see what efforts are being made by teachers and schools to instill such character education. This research is qualitative description research with 29 research subjects as grade XII students. The instrument used was in the form of a questionnaire and several interview questions. The results showed that the picture of biology learning character education in Genetic Engineering material in State Senior High School 7 Bengkulu had begun to be embedded but still needed guidance to be more focused on understanding the concepts, impacts, and application of genetic engineering techniques because teachers had not fully applied the teaching methods of character education in class. The picture can be seen in the observation data, questionnaires, and interviews of honest, disciplined, democratic, communicative, and creative valuesÂ that have begun to develop. Caring, responsibility, and sociality are well entrenched. Independence is still very much needed to be considered while religious have begun to appear. In an effort to create character education attitudes that will be the basis for dealing with scientific and technological progress, the school has also implemented a number of support programs to improve or train character education attitudes